2017
DOI: 10.3389/fnsys.2017.00025
|View full text |Cite
|
Sign up to set email alerts
|

Cortico-Striatal-Thalamic Loop Circuits of the Orbitofrontal Cortex: Promising Therapeutic Targets in Psychiatric Illness

Abstract: Corticostriatal circuits through the orbitofrontal cortex (OFC) play key roles in complex human behaviors such as evaluation, affect regulation and reward-based decision-making. Importantly, the medial and lateral OFC (mOFC and lOFC) circuits have functionally and anatomically distinct connectivity profiles which differentially contribute to the various aspects of goal-directed behavior. OFC corticostriatal circuits have been consistently implicated across a wide range of psychiatric disorders, including major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
164
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(180 citation statements)
references
References 240 publications
(398 reference statements)
5
164
0
3
Order By: Relevance
“…A significant case-control brain volume difference was observed for a brain component localized to bilateral fronto-striatal white matter, adjacent to the orbitofrontal cortex. Frontostriatal circuits are implicated in complex behaviors, such as reward processing, emotion regulation, inhibition, and motivational states (37), and the dysfunction of these circuits is implicated in several psychiatric disorders (37)(38)(39), including ADHD (40). Previous structural MRI studies have shown volume reductions in frontal lobes and the striatum (10,13) in individuals with ADHD compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…A significant case-control brain volume difference was observed for a brain component localized to bilateral fronto-striatal white matter, adjacent to the orbitofrontal cortex. Frontostriatal circuits are implicated in complex behaviors, such as reward processing, emotion regulation, inhibition, and motivational states (37), and the dysfunction of these circuits is implicated in several psychiatric disorders (37)(38)(39), including ADHD (40). Previous structural MRI studies have shown volume reductions in frontal lobes and the striatum (10,13) in individuals with ADHD compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…43 The DLPFC plays an essential role in emotional, motivational, attentional, and executive functions. 44 Gray matter volume reductions have also been found in the DLPFC in MDD patients compared to healthy controls. 2 Brain activity in the DLPFC was also found to be decreased 13 and could be increased to the average level after antidepressant treatment.…”
Section: Frontal Lobementioning
confidence: 99%
“…Fibers extending through the bilateral medial frontal lobe to the anterior corpus callosum and passing fibers connecting the medial frontal lobe to the amygdala via the uncinate fasciculus during stimulation of the “best” contacts have been deemed to be the switch in MDD . The DLPFC plays an essential role in emotional, motivational, attentional, and executive functions . Gray matter volume reductions have also been found in the DLPFC in MDD patients compared to healthy controls .…”
Section: Significant Structural Brain Alterations In Mddmentioning
confidence: 99%
“…One prototypical adaptive behaviour is value-guided decisionmaking, which relies on diverse neural systems thought to realise key computations, such as the assignment of value to specific stimulus-action pairs based on rewardhistory. Failure to adapt behaviour is a common symptom in many neurological disorders such as autism and schizophrenia 1 . In mammals, value-guided decisionmaking is governed by distributed neural circuits engaging cognitive primitives in prefrontal areas of the neocortex 2,3 .…”
Section: Main Textmentioning
confidence: 99%